Financial Accountability of Dayah in Aceh Province: Its Meaning and Practice - Uun Dwi Al Muddatstsir; Marliyah Marliyah; Asmuni Asmuni (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
This study aims to examine the accountability perspectives and practices of financial reporting within dayah institutions in Aceh. The object of this study is dayah institutions located in Langsa City, East Aceh, and Aceh Tamiang. Data were gathered using in-depth interviews with the informants that were selected using purposive sampling with criteria: being a middle-upper management in one of these institutions and have involved in the production of accounting reports. In analyzing the data, the study employs the Miles and Huberman model along with Nvivo Software. The findings reveal that dayah's perspective on financial responsibility is a moral concept that upholds the values of integrity, communicativeness, and concern for meeting organizational duties regarding the use of public funds. In terms of accountability practice, it has not fully complied with the financial accounting standards outlined in PSAK 45 by the Institute of Indonesia Chartered Accountants (IAI), particularly with regard to the financial statements of non-profit entities, which include the disclosure of financial statements, activity reports, cash flow statements, and notes to financial statements. Consequently, it is imperative to expedite the improvement of financial reporting in dayah institutions.======================================================================================================== ABSTRAK - Akuntabilitas Keuangan Dayah di Aceh: Pemahaman dan Praktiknya. Penelitian ini bertujuan untuk memberikan gambaran dan pemahaman tentang perspektif akuntabilitas keuangan pada lembaga dayah di provinsi Aceh serta praktik akuntabilitas keuangan yang dilakukannya. Pendekatan penelitian yang dilakukan adalah kualitatif dengan teknik analisis data yang dikembangkan oleh Miles dan Huberman serta di kombinasikan dengan alat analisis Software Nvivo. Objek penelitian adalah lembaga dayah yang ada di Kota Langsa, Aceh Timur dan Aceh Tamiang. Informan penelitian ini adalah para pimpinan dayah dan pihak yang terlibat dalam pembuatan laporan keuangan dayah. Hasil penelitian memberikan gambaran bahwa perspektif dayah tentang akuntabilitas keuangan adalah suatu konsep akhlak yang menjunjung tinggi nilai integritas, komunikatif, dan kepedulian untuk memenuhi pertanggungjawaban organisasi dalam menggunakan dana publik. Praktik akuntabilitas belum memenuhi standar akuntansi keuangan yang digariskan dalam PSAK 45, khususnya dalam hal pengungkapan laporan keuangan, laporan aktivitas, laporan arus kas, dan catatan atas laporan keuangan. Oleh karena itu, diperlukan upaya-upaya yang dapat mempercepat perbaikan laporan keuangan pada lembaga dayah di Aceh.